Lateral flow assays: Progress and evolution of recent trends in point-of-care applications - Saloni Kakkar; Payal Gupta; Shiv Pratap Singh Yadav; Divakar Raj; Garima Singh; Sakshi Chauhan; Manoj Kumar Mishra; Elena Martín-Ortega; Stefano Chiussi; Krishna Kant (Materials Today Bio, 2024)
Paper based point-of-care (PoC) detection platforms applying lateral flow assays (LFAs) have gained paramount approval in the diagnostic domain as well as in environmental applications owing to their ease of utility, low cost, and rapid signal readout. It has centralized the aspect of self-evaluation exhibiting promising potential in the last global pandemic era of Covid-19 implementing rapid management of public health in remote areas. In this perspective, the present review is focused towards landscaping the current framework of LFAs along with integration of components and characteristics for improving the assay by pushing the detection limits. The review highlights the synergistic aspects of assay designing, sample enrichment strategies, novel nanomaterials-based signal transducers, and high-end analytical techniques that contribute significantly towards sensitivity and specificity enhancement. Various recent studies are discussed supporting the innovations in LFA systems that focus upon the accuracy and reliability of rapid PoC testing. The review also provides a comprehensive overview of all the possible difficulties in commercialization of LFAs subjecting its applicability to pathogen surveillance, water and food testing, disease diagnostics, as well as to agriculture and environmental issues.